Dejavniki zaviranja pritožb potrošnikov in njihov pomen za podjetja - Murovec, Nika (Naše gospodarstvo, 2006)
Consumer complaints represent a significant source of information for companies. Since many consumers do not file a complaint when they are dissatisfied, companies should (1) know which factors hinder consumer complaints, and (2) try to eliminate or at least minimize the influence of these factors. Only by doing that, companies ensure themselves appropriate feedback from consumers so that they can increase customer satisfaction and consequently their own profit. Based on data obtained through personal interviews with 253 consumers, we determined which of the factors that hinder consumer complaints are relevant for companies in Slovenia. Some of these factors are specific for Slovenian consumers.
Keywords: podjetja; kupci; potrošniki; zadovoljstvo; pritožbe; psihologija potrošnika